Effects of sinusoidal magnetic field on adherence inhibition of leucocytes: preliminary results - Jandová, A; Hurych, J; Nedbalová, M; Trojan, S; Dohnalová, A; Cocek, A; Pokorný, J; Trkal, V (Bioelectrochemistry and bioenergetics (Lausanne, Switzerland), 1999)
The leucocyte surface properties manifest the cell-mediated immunity. The response of the cell-mediated immunity to external magnetic field was examined by observing leucocyte adherence to solid state surfaces. In the presence of antigen, leucocytes taken from cancer patients exhibit decreased adherence in contrast with adherence of leucocytes from healthy humans. After 1 h exposure to a sinusoidal magnetic field of 50 Hz and of 1 mT or 10 mT, adherence of leucocytes taken from cancer patients is strongly increased. The 1 mT magnetic field has stronger effect than the 10 mT field.
Keywords: Neoplasms; buněčná imunita; Magnetics; buněčná adheze; studie případů a kontrol; CD4-pozitivní T-lymfocyty; Cell Adhesion; Humans; Immunity, Cellular; nádory; magnetismus; CD4-Positive T-Lymphocytes; lidé; Case-Control Studies